1988
DOI: 10.1136/jcp.41.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and low osteocalcin concentrations in anorexia nervosa.

Abstract: the patients had had pathological fractures. All patients except one had a daily calcium intake of less than 50 mg daily, and a dietary vitamin D intake ofless than 50 IU daily. One patient was taking regular supplements of vitamin D. All had plasma urea and creatinine concentrations within the normal range for our laboratory. Seventeen age and sex matched healthy volunteers were also studied as controls. All controls had body weights within 10% of the average body weight appropriate for height (Geigy Scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 13 publications
1
33
0
5
Order By: Relevance
“…In K, 3 wk of nutritional rehabilitation produced a significant rise in both of these proteins (6), suggesting that serum osteocalcin level is sensitive to nutritional status. This is strengthened by the low osteocalcin levels found in patients suffering from anorexia nervosa (22), in 3-day starved rats (21), or after 4 wk of dietary restriction in rats (23), whereas high osteocalcin levels are found in obese children fed an energy-rich diet (24). Michaelsen et al (25) have found a positive correlation between serum osteocalcin and milk intake in a study of 2-to 9-mo-old breast-fed babies.…”
Section: Discussionmentioning
confidence: 88%
“…In K, 3 wk of nutritional rehabilitation produced a significant rise in both of these proteins (6), suggesting that serum osteocalcin level is sensitive to nutritional status. This is strengthened by the low osteocalcin levels found in patients suffering from anorexia nervosa (22), in 3-day starved rats (21), or after 4 wk of dietary restriction in rats (23), whereas high osteocalcin levels are found in obese children fed an energy-rich diet (24). Michaelsen et al (25) have found a positive correlation between serum osteocalcin and milk intake in a study of 2-to 9-mo-old breast-fed babies.…”
Section: Discussionmentioning
confidence: 88%
“…However, TGF-β1 stimulates vitamin D receptor expression in mature osteoblast cell line. Fonseca et al [48] reported prevalent vitamin D insufficiency in young women with AN. Calcium and vitamin D intake among patients with AN is presumably low due to dietary restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca et al measured serum vitamin D concentrations in 17 young adults with AN [6]. The participants' dietary intake was less than 50 IU daily and only one patient was receiving vitamin D supplementation; the median serum concentration of 25-hydroxyvitamin D (25OHD) was significantly lower than controls.…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D status of teenagers with AN, with its implications for bone health, has only been examined previously in small studies [4,[6][7][8]. Fonseca et al measured serum vitamin D concentrations in 17 young adults with AN [6].…”
Section: Introductionmentioning
confidence: 99%